Exploring Relationships among Proactiveness, Risk‐Taking and Innovation Output in Family and Non‐Family Firms. Issue 2 (26th January 2014) - Craig, Justin B.; Pohjola, Mikko; Kraus, Sascha; Jensen, Søren H.
<x xml:space="preserve">Abstract</x> In an empirical investigation of 532 Finnish firms, and using the entrepreneurial orientation (EO) literature to frame our arguments, we demonstrate that relationships among proactivity, risk‐taking and innovation output differ in family and non‐family firms. Specifically, we find evidence that risk‐taking does not affect innovation output in family firms, whereas in non‐family firms, innovation output is increased through risk‐taking. Also, proactive family firms influence their innovation output more positively than proactive non‐family firms do. This study adds important new insights to the growing knowledge of EO, which are discussed in the following for both academic and business audiences.